Ampolas de Vidro: Riscos e Benefícios - Carraretto, Antônio Roberto [UNESP]; Curi, Erick Freitas; de Almeida, Carlos Eduardo David; Abatti, Roberta Eleni Monteiro (Elsevier, 2011)
Background and objectives: Glass ampoules have been widely used in packaging injection drugs. Glass has important characteristics that allow it to be widely used in fabrication of recipients for drugs and other sterile substances. However, contamination of solutions with glass microparticles on breaking open glass ampoules, the presence of metals, percutaneous injury, and biological contamination justify the need of educational materials to orient the manipulation of ampoules. Contents: Glass microparticles generated in the snap-opening of ampoules, as well as metals that contaminate their contents can be aspirated and injected through several routes. Exogenous contaminations by glass and metals can reach several sites in the organism. They trigger organic reactions that may give rise to injuries. Opening ampoules can expose professionals to the risk of percutaneous injuries. These lesions increase the biological risk as they are the gateway for viruses and bacteria. Ampoules opening systems (VIBRAC and OPC) have been developed to reduce the incidence of such accidents. Alternative materials to glass may represent an interesting strategy to increase safety. The use of prefilled syringes may represent an evolution regarding safety. Conclusions: Team training and information provided by the pharmaceutical industry on the use of ampoules are fundamental in the prophylaxis of accidents and contaminations. The search for safer materials to replace glass is also important. © 2011 Elsevier Editora Ltda.
Glass Ampoules: Risks and Benefits
Keywords: Anesthesiology; Disposable equipment; Education, medical, continuing; Glass; Safety management; glass; accident; ampoule; contamination; drug packaging; risk; Drug Contamination; Drug Packaging; Health Personnel; Occupational Injuries; Risk Factors; Risk Management